Healthcare Financing and Hospitals Sustainability – The Case of Poland - Apolonia Jaskólska; Małgorzata Cygańska; Renata Burchart adiunkt; Izabela Borkowska (Communications of International Proceedings, 2023)
The healthcare system in Poland is facing a large number of various problems. The main ones include staff shortages among doctors, nurses and midwives, insufficient healthcare system funding by the state and long waiting times for a visit to a specialist. The discussion, however, has been mainly limited to “traditional” issues of cost-effectiveness, quality of care, and, lately, patient involvement. This study analyses the impact of changing the rules of financing healthcare entities on their financial condition. The problem is crucial not only from the micro perspective relating to the situation of single institutions. Still, it has fundamental meaning for improving the economic sustainability of the whole healthcare system. The first part of the paper characterizes the legislation process leading to changing the healthcare entity financing rules after 2017. Subsequently, the financial condition of ten selected hospitals during the periods 2013-2016 and 2018-2019. The last step involves an analysis of the impact exerted by the change in the rules of financing hospitals on their financial condition. This assessment was performed with the Mann-Whitney U test. The results led the researchers to the following conclusion: a change in healthcare entity financing did not have a considerable impact on the financial results of the entities under study. Only two out of the nine ratios under study changed considerably during the periods before and after introducing the change in the financing rules.
Keywords: Rules of financing hospitals; healthcare entities; economic and financial condition; economic and financial ratios of the hospitals.